2017
DOI: 10.18632/oncotarget.16968
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and surgical treatment of sacral schwannomas

Abstract: BackgroundSacral schwannoma is relatively rare and both the early diagnosis and appropriate treatment of sacral schwannomas are equally very challenging.Methods11 sacral schwannoma cases operated at the Second Affiliated Hospital, School of Medicine, Zhejiang University, from 2012 to 2016, were investigated retrospectively and 10 were followed up. All patients were assessed with X-ray, CT and MRI, and underwent an intralesional excision.ResultsOne patient was male, nine were female and the average age was 48 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…For type I tumors which are mostly confined to the sacrum, complete resection can be achieved via posterior approach alone; unlike type I tumor, type II sacral tumors originate in the sacrum but metastasize towards the presacral and subcutaneous region, and consequently combined anterior–posterior approach is necessary; type III tumor is located in the presacral or retroperitoneal alone, which an anterior approach is appropriate. Though some authors reported satisfying results without local recurrence can be obtained via piecemeal surgery with sacral nerve roots being preserved, 17 en‐bloc resection of the tumor was still recommended in most literature of MS for its excellent local control. However, given the origin, location, as well as the extent of intraosseous invasion of the MS, it is difficult to ensure a complete tumor removal while maintaining nerve integrity, and thus presumably pose a great impact on the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…For type I tumors which are mostly confined to the sacrum, complete resection can be achieved via posterior approach alone; unlike type I tumor, type II sacral tumors originate in the sacrum but metastasize towards the presacral and subcutaneous region, and consequently combined anterior–posterior approach is necessary; type III tumor is located in the presacral or retroperitoneal alone, which an anterior approach is appropriate. Though some authors reported satisfying results without local recurrence can be obtained via piecemeal surgery with sacral nerve roots being preserved, 17 en‐bloc resection of the tumor was still recommended in most literature of MS for its excellent local control. However, given the origin, location, as well as the extent of intraosseous invasion of the MS, it is difficult to ensure a complete tumor removal while maintaining nerve integrity, and thus presumably pose a great impact on the patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of conventional IOSs, several authors reportedly prefer the piecemeal subtotal excision with sacral nerve roots of origin preserved as much as possible, which could achieve a good outcome without local recurrence and transformation to malignancy. 19) However, all available literatures of MSs recommend complete surgical excision. En-bloc resection may provide excellent local control in this locally aggressive tumor 21) and we attempted to achieve En-bloc resection via posterior approach while small part of the tumor inside the sacrum needed to be additionally resected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the procedure has a potential risk of complications such as infection, hemorrhage, site-related problems, and wound closure issues, it was significantly helpful for the predetermination of the nature of the tumor in consideration of MS due to its atypical imaging findings. 8,19) As we all know, misdiagnosis of the disease will gradually promote tumor growth, making the operating procedure more difficult. Klimo et al proposed a classification of sacral nerve sheath tumors based on their location into three types (Types I-III).…”
Section: Discussionmentioning
confidence: 99%
“…Sacral schwannomas are rare tumors that are treated surgically when symptomatic with a great outcome, yet not all patients are surgical candidates [1,2]. Pre-existing conditions or tumor location may limit a patient's surgical options.…”
Section: Introductionmentioning
confidence: 99%